The Role of Image Processing in Measuring Fractal Dimension - ,i M.N, Suk; N.S, Mohamed,; Ali, S.A, Hashim; Zainuddin, Roziati (Malaysian Journal of Science, 2007)
The characterization of irregular objects with fractal methods often leads to the estimation of the slope of a function plotted against a scale parameter. The slope is usually obtained with a linear regression with upper and lower boundaries that sets the acceptable range of fractal dimension value. This pattern is similar even when the variables are changed. In the present work, we developed a computer application to measure fractal dimension, with emphasis on medical images. The system has the ability to process the images involving the Red, Green, Blue (RGS) and the Hue, Saturation, (luminosity) Value (HSV) before any analysis of the image(s) is carried out. The results of the present work suggest a boundary (which determines how much image processing should be done in order to achieve relevant fractal dimension values) can be identified by systematically changing the parameter.